2017
DOI: 10.1016/j.cocis.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Novel food grade dispersants: Review of recent progress

Abstract: Many foreseen advances in the design of food structures, suitable for ever demanding nutrient delivery systems, tailored controlled release, microencapsulation and protection of active ingredients, require a generation of superior dispersants than those currently provided by proteins. While the most efficient structure for such dispersants is relatively easy to specify, in foods they cannot simply be synthetically manufactured. The review highlights several possible strategies for realising more efficient food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Low and high molecular weight surfactants have been extensively used to stabilize emulsions but there has been recently a great demand for the Pickering emulsions. These emulsions are conventionally stabilized using solid particles, which have partial wettability to two lipid and aqueous phases (Ettelaie, Zengin, & Lishchuk, 2017;Wang & Heuzey, 2016). Colloidal complexes with partial wettability, which are able to accumulate at the interface to prevent coalescence or Ostwald ripening can be utilized to induce the Pickering stabilization (Ettelaie & Murray, 2015;Lu, Zhang, Li, & Huang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Low and high molecular weight surfactants have been extensively used to stabilize emulsions but there has been recently a great demand for the Pickering emulsions. These emulsions are conventionally stabilized using solid particles, which have partial wettability to two lipid and aqueous phases (Ettelaie, Zengin, & Lishchuk, 2017;Wang & Heuzey, 2016). Colloidal complexes with partial wettability, which are able to accumulate at the interface to prevent coalescence or Ostwald ripening can be utilized to induce the Pickering stabilization (Ettelaie & Murray, 2015;Lu, Zhang, Li, & Huang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the antioxidant activity of Qct was higher in nanoparticle form than in normal Qct . In another study by Bagad and Khan, it is reported that the Qct in nano form maintained a sustained release of Qct and displayed an enhancement of bioavailability by 2.38 to 4.93 fold when compared with pure quercetin . However, it may be noted that many of these nanoparticle formulations were prepared either by using several synthetic compounds or some toxic preparation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…This is proven to be a safe, economical and effective strategy to produce protein fragments with significantly improved solubility, and thus also often superior emulsifying abilities than the original intact proteins. 6,20,23 Moreover, compared to native proteins from which they are derived, fragmented plant proteins also seem to be more suitable for synthesizing conjugates with polysaccharides via Maillard reactions. Such conjugates are produced when covalent bonds are formed between protein fragments and the polysaccharides.…”
Section: Introductionmentioning
confidence: 99%